What is this thing called community scientific culture? An approach and a model of analysis - Núñez Castro, Andrés Manuel; Gómez Ferri, Javier (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Academic interest in the study of the scientific culture of citizens reflects a scholarly and political concern for the unequal social distribution of scientific knowledge. The predominant approach has treated scientific culture as an individual entity. We propose a model for the study of scientific culture as a community entity. To prove this, we have applied the model to a case: El Tablero (Tenerife). Based on this case, we have evidenced how the community has developed new concepts in order to face the problems posed, consolidating an agricultural alternative based on the inherited rural culture, integrating local identity and legitimized knowledge.